Upah Pekerjaan Membangun Rumah Ibadah Nonmuslim di Lingkungan Mayoritas Muslim dalam Perspektif Hukum Islam - Ahmad Syaripudin; Zulfikar Alim Said (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to find out and understand the wage law for building a house of worship for other religions in the perspective of Islamic law with the following details, namely; First, what is the view of Islam on wages. Second, how does the law take wages from the construction of houses of worship for religions other than Islam in the perspective of Islamic law. This type of research is qualitative-descriptive. Qualitative is seen as a research method that usually produces descriptive data, namely in the form of written or spoken words from the data studied. The descriptive research method aims to make a description, namely a systematic, factual and accurate picture or painting of the phenomenon or relationship between the phenomena being investigated and includes library research because this study completely requires a study of the written works of experts who related to the discussion. This research is also normative because it will examine the texts of the Qur'an and Hadith or the thoughts of scholars related to the discussion. The results of this study based on the study found that: First, the law of wages or ijarah in the view of Islam is something that is permissible because it is part of of muamalah where the basis is permissible. It is strengthened that wages or Ijarah are clearly mentioned in the Qur'an and hadith as well as the consensus of the scholars who show their abilities. Second, it is permissible to take wages from the work of building a house of worship for a religion other than Islam, from the perspective of Islamic law, if the worker is in a dharurah condition with the following limitations, which are a reflection of the following conditions: (1) in a very hungry condition, and no food is found to sustain them. life. (2) is forced by someone to eat what is unlawful, so that the unlawful becomes lawful for him.